2016
DOI: 10.1063/1.4967639
|View full text |Cite
|
Sign up to set email alerts
|

Multi-dimensional validation of a maximum-entropy-based interpolative moment closure

Abstract: Articles you may be interested inComparison of maximum entropy and quadrature-based moment closures for shock transitions prediction in onedimensional gaskinetic theory AIP Conf.Abstract. The performance of a novel maximum-entropy-based 14-moment interpolative closure is examined for multidimensional flows via validation of the closure for several established benchmark problems. Despite its consideration of heat transfer, this 14-moment closure contains closed-form expressions for the closing fluxes, unlike th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The rationale behind this approximation is that, if k is large enough, the simulation should remain stable. This approach has the benefit of being simple, and was shown to be profitable in a number of conditions (see for instance 68 ). However, this approximation is not suitable for the present work, where the high rarefaction and supersonic speeds let the system depart significantly from equilibrium and also approach the Junk subspace.…”
Section: Preprint Preprintmentioning
confidence: 99%
“…The rationale behind this approximation is that, if k is large enough, the simulation should remain stable. This approach has the benefit of being simple, and was shown to be profitable in a number of conditions (see for instance 68 ). However, this approximation is not suitable for the present work, where the high rarefaction and supersonic speeds let the system depart significantly from equilibrium and also approach the Junk subspace.…”
Section: Preprint Preprintmentioning
confidence: 99%
“…However, recent developments have provided approximated interpolative approaches to the entropy maximisation problem, which allow for an agile and affordable solution to be found for selected systems of equations, 38 and their application to multi-dimensional non-equilibrium gaseous flows has yielded very promising results. 39,40 In this work, we consider a 14-moment maximumentropy description for the electron population. 24,38,41 First, in Section II we discuss the kinetic equation and provide a brief description of the maximum-entropy framework, together with the system of 14 moments adopted here.…”
Section: A Proposed Description and Structure Of This Workmentioning
confidence: 99%
“…Journal of Geophysical Research: Space Physics remaining quantities to close the fluid equations (McDonald, 2016;McDonald & Torrilhon, 2013;Tensuda et al, 2016). It has also been shown that there can exist physically realizable states which cannot be described by Equation 7, though it is possible to guarantee realizability by slightly modifying the distribution (Groth & McDonald, 2009;Junk, 1998;McDonald & Groth, 2013;Schaerer & Torrilhon, 2015).…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%